Corporate violations of human rights and the environment in developing markets: exploring the role of corporate law - Ojogbo, Samuel E. (2018)
This thesis addresses the problem of environmental degradation and human rights abuses by Multinational Corporations (MNCs) operating in developing markets, which has been attributed to the difficulty in regulating modern MNCs. Three main factors that create the environment for corporate impunity for human rights and environmental abuse in developing markets as identified by current scholarship are the mismatch between the modern corporate structure and the rules of corporate law, the insensitivity of the governments of developing markets to the plight of human rights victims, and the general lack of access to judicial and administrative remedies. However, even though the current corporate legal architecture is one of the factors that contribute to corporate human rights and environmental regulatory challenge, emerging regulatory initiatives that seek to address the problem do not consider corporate law reform as one of the options that could resolve the challenge. This thesis challenges the current scholarship and regulatory focus on remedial solution to the problem and investigates existing regimes. This investigation focuses on two areas. First, it focuses on international human rights law and international environmental law, and, secondly, on the legal and regulatory regimes concerned with the corporation, human rights and the environment in Nigeria and selected major developed market jurisdictions. The thesis identifies the current procedures for applying international norms to MNCs as the major problem with the international regimes, and the weak and inefficient enforcement infrastructure in Nigeria and other developing markets as the major problem with holding MNCs accountable for human rights and environmental abuses in developing markets. As a result, the thesis argues that the regulatory challenge could be addressed by focusing on MNC activities at the national level, and suggests a shift from the remedial focus of the current regimes to a preventative approach. The thesis proposes a review of the corporate legal architecture to incorporate the group that is most affected by corporate externalities into corporate boards because that is where the decisions that generate the abuses are made. The thesis concludes with a blueprint for the proposed structure which is aimed at promoting responsible human rights and environmental friendly decision-making as a means of injecting human rights responsibility into corporate decision making, and addressing the problem of corporate human rights and environmental abuses, especially in developing markets.